Preparation method and application of atomic layer deposition synergistically doped modified sodium vanadate
By introducing metal cations and PO43- groups between the layers of the HNaV6O16·4H2O cathode material, and using atomic layer deposition technology to coat the metal oxide, the problems of low electronic conductivity and slow sodium ion diffusion rate of the material are solved, significantly improving improved its cycle stability and rate performance.
Patent Information
- Application Number
- CN202310391862.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-12
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-04-12
AI Technical Summary
As the positive electrode material of sodium ion battery, HNaV6O16·4H2O has problems with low electron conductivity and slow diffusion rate of sodium ion, resulting in faster capacity decay and poor rate performance during the cycle.
By introducing metal cations and PO43- groups between layers, its electronic conductivity and ionic conductivity are improved, and metal oxide coating is achieved through atomic layer deposition technology to improve the cycle stability of the material.
The electronic conductivity and ionic conductivity of HNaV6O16·4H2O are significantly improved, its cycle life is extended, and the rate performance and Coulombic efficiency are improved.
Smart Images

Figure CN116282153B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the atomic layer deposition technology to cooperate with transition metal cations and phosphate ions to co-embed HNaV6O 16 ·4H2O powder technology field, involving a preparation method of atomic layer deposition synergistically doped modified sodium vanadate.
[0002] The present invention also relates to the application of composite powder prepared by the preparation method of atomic layer deposition synergistically doped modified sodium vanadate in sodium ion batteries. Background Art
[0003] In recent years, efficient energy storage systems have attracted people's attention. With the continuous exploration of clean and renewable energy, lithium-ion batteries have dominated the portable and smart electronic device market for nearly three decades; this is mainly due to their high energy and power density, long cycle life and environmental friendliness; however, due to the shortage of lithium resources in the earth's crust, high cost and geographical distribution, a candidate for lithium-ion batteries is needed; therefore, sodium-ion batteries have regained people's attention, mainly because of the abundance of sodium resources and similar electrochemical mechanisms; therefore, sodium-ion batteries are considered to be an ideal alternative to lithium-ion batteries. However, the energy density of sodium-ion batteries is lower than that of lithium-ion batteries, as well as the safety issues caused by the use of Na in sodium-ion batteries. During the discharge and charging process, it is necessary to explore the possibility of accommodating a larger radius. The development of cathode materials for Na+ is a huge challenge; exploring and optimizing cathode materials with suitable voltage window, high reversible capacity and stable structure is of great significance for the application of sodium-ion batteries;
[0004] The cathode materials of sodium-ion batteries mainly include layered transition metal oxides, polyanionic compounds, Prussian blue, etc., while vanadium-based cathode materials have attracted more attention due to their high operating voltage, theoretical capacity and energy density. All the pentavalent electrons of V atoms can participate in bonding, thus generating V 2+ To V 5+ In addition to the rich electrochemical valence of V, the low price and abundant sources of V-based materials also make them potential cathode materials for sodium-ion batteries. So far, the vanadium-based materials reported mainly include vanadium oxides, vanadium bronzes, and vanadium-based phosphates. As a vanadium bronze, HNaV6O 16 ·4H2O cathode material, which is composed of [V3O8] layers, with sodium ions located in octahedral vacancies, playing a supporting role between layers and stabilizing the crystal structure, is a cathode material for sodium ion batteries with great development potential. However, its low electronic conductivity and slow sodium ion diffusion rate lead to rapid capacity decay and poor rate performance during the cycle process;
[0005] As one of the most commonly used and effective modification strategies, the interlayer pre-embedding of metal cations has been widely used. The successful pre-embedding of metal cations in the interlayer can stabilize the layer structure as an ion column and regulate the electronic structure of lattice oxygen, thereby improving the conductivity of the compound. In addition, the introduction of NH4 + PO4 3- Plasmon groups can significantly increase the interlayer spacing, stabilize the crystal structure, and reduce Na + The migration activation energy during heavy discharge increases, thereby improving the ion migration kinetics during charge and discharge. In addition, due to the dissolution of vanadium during charge and discharge, the decomposition of electrolyte under high pressure (or high temperature) and particle pulverization often cause HNaV6O 16 ·Capacity decay of 4H2O. A major factor inducing vanadium dissolution is the corrosion of trace HF in the liquid electrolyte. The dissolution of vanadium will destroy HNaV6O 16 ·The crystal structure of 4H2O leads to irreversible capacity decay or low Coulombic efficiency. Subsequently, vanadium ions in the liquid electrolyte may be deposited on the anode surface, thereby increasing the battery impedance or destroying the solid electrolyte interface (SEI) layer. Surface modification is an effective method to inhibit vanadium dissolution, and atomic layer deposition technology is an effective and efficient surface modification technology. Through precise control at the atomic level, a stable, uniformly distributed and dense metal oxide layer is obtained. The presence of the metal oxide layer can effectively inhibit the destruction of the crystal structure caused by vanadium dissolution caused by HF corrosion, and can effectively inhibit the lattice collapse caused by volume expansion during the charge and discharge process, which greatly improves the Coulombic efficiency and cycle stability of the positive electrode material. Therefore, for HNaV6O 16 ·4H2O is used as the positive electrode material of sodium ion battery. The present invention introduces metal cations and PO4 3- The groups improve its electronic conductivity and ionic conductivity, and the metal oxide coating achieved by atomic layer deposition technology improves its cyclic stability, with obvious improvement effects. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing modified sodium vanadate by atomic layer deposition synergistic doping, which solves the problem of HNaV6O 16 ·4H2O as a positive electrode material for sodium-ion batteries has the problem of vanadium dissolution caused by HF corrosion, which leads to the destruction of the crystal structure.
[0007] The technical solution adopted by the present invention is a method for preparing sodium vanadate modified by atomic layer deposition and coordinated doping, which is specifically implemented according to the following steps:
[0008] Step 1, weighing vanadium oxyphosphate monohydrate, dispersing it in deionized water and ultrasonically treating it to obtain solution A;
[0009] Step 2, weighing cobalt acetate tetrahydrate, nickel acetate tetrahydrate and anhydrous sodium iodide and adding them to solution A to obtain solution B;
[0010] Step 3, subjecting solution B to ultrasonic treatment;
[0011] Step 4, pour the ultrasonicated solution B into the inner lining of the reaction kettle, then fix the inner lining in the outer kettle, put it into a blast drying oven, dry it, and then wash it;
[0012] Step 5: After vacuum drying, the product is collected and ground to obtain HNaV6O co-embedded with cobalt ions, nickel ions and phosphate ions. 16 4H2O powder sample.
[0013] Step 6: HNaV6O co-embedded with cobalt ions, nickel ions and phosphate ions 16 4H2O powder is placed in the ALD reaction chamber, vacuumed and heated;
[0014] Step 7: In a vacuum environment, inert gas carries TMA vapor and deposits it on HNaV6O co-embedded with cobalt ions, nickel ions and phosphate ions. 16 4H2O particle surface;
[0015] Step 8: The inert carrier gas at a specific flow rate transports the cobalt ions, nickel ions and phosphate ions into the HNaV6O 16 The physically adsorbed TMA on the surface of 4H2O particles is blown off, leaving a layer of chemically adsorbed TMA;
[0016] Step 9: Water uses its own vapor pressure to co-intercalate HNaV6O with cobalt ions, nickel ions and phosphate ions. 16 The TMA adsorbed on the surface of 4H2O particles undergoes redox reaction;
[0017] Step 10: The inert carrier gas at a specific flow rate transports the cobalt ions, nickel ions and phosphate ions into the HNaV6O 16 ·Blow away the byproducts and excess water molecules on the surface of the 4H2O particles; after standing, purge the chamber with inert gas to complete an ALD cycle. Perform multiple cycles under the same deposition conditions to complete the deposition of Al2O3 of the specified thickness.
[0018] The present invention is also characterized in that:
[0019] In step 1, 250-350 mg of vanadium oxyphosphate monohydrate is weighed and dispersed in 30-40 ml of deionized water, and ultrasonicated for 0.5 h to 1.5 h at a power of 80-120 W at room temperature;
[0020] In step 2, 7.50-8.0 mg of cobalt acetate tetrahydrate and nickel acetate tetrahydrate and 90-95 mg of anhydrous sodium iodide are weighed and added to solution A to obtain solution B, cobalt acetate tetrahydrate and nickel acetate tetrahydrate are micro-adjusted, and the weighing instrument is an analytical balance;
[0021] Step 3 specifically comprises ultrasonicating solution B for 1 h to 3 h at an ultrasonic power of 80 to 120 W at room temperature until the solution gradually changes from wine red to black;
[0022] The drying temperature in step 4 is 140-160° C., the reaction time is 11-13 h, and the washing process is specifically as follows: the product is washed alternately with water 2-4 times and alcohol 2-4 times, the water and alcohol washing is mainly performed by suction filtration or centrifugation, and the collection is also mainly performed by suction filtration or centrifugation;
[0023] The vacuum conditions in step 5 are: 50-70°C, drying for 11-13h, and before vacuum drying, sealing with plastic wrap, and punching holes in the plastic wrap to ensure sufficient drying under low pressure conditions;
[0024] In step 6, the powder sample is vibrated and dispersed before being added to the reaction chamber, and the temperature is raised to 110-130° C.;
[0025] In step 7, the inert gas flow rate is 40 ml / min, the duration is 50 to 70 s, and the reaction steam source can be TMA, DEZ, Fe(cp)2, TiCl4, etc.;
[0026] Wherein the inert gas flow rate in step 8 is 80 ml / min, and the blow-off time is 110 to 130 s;
[0027] In step 9, the water injection time is 60s;
[0028] In step 10, the inert gas flow rate is 80 ml / min, and the introduction time is 110 to 130 s.
[0029] The second technical solution adopted by the present invention is that the metal cations and phosphate ions are co-embedded HNaV6O prepared by the preparation method of atomic layer deposition synergistically doping modified sodium vanadate. 16 Application of 4H2O in sodium ion batteries.
[0030] The beneficial effects of the present invention are
[0031] (1) Since the present invention adopts a one-step hydrothermal reaction to directly synthesize the initial target powder, it has a low synthesis temperature and a simple synthesis path, and does not require large equipment and harsh reaction conditions;
[0032] (2) The vanadium source and phosphorus source used in the present invention are vanadium oxyphosphate monohydrate, the sodium source is anhydrous sodium iodide, and the solvent is deionized water. These three substances are common raw materials, cheap and easy to obtain, and low in cost. The entire reaction is easy to control and environmentally friendly, and the product does not require post-processing, which is suitable for large-scale production;
[0033] (3) The atomic layer deposition technology used in the present invention finely controls the thickness of metal oxides at the atomic scale, and the technology is mature and has strong repeatability;
[0034] (4) The present invention strictly coordinates and controls the concentration and ratio of vanadium source, phosphorus source, sodium source, cobalt salt, and nickel salt, reaction temperature, reaction time and other parameters, and fully utilizes the reaction of vanadium source, sodium source, cobalt source, and nickel source, so that cobalt ions, nickel ions, and phosphate ions are co-embedded in HNaV6O 16 4H2O nucleates and grows uniformly in deionized water, producing a petal structure of about 4um in size assembled from nanosheets with a width of about 200nm and a thickness of about 4nm;
[0035] (5) Effect of the amount of cobalt and nickel salt added on the HNaV6O co-embedded with cobalt ions, nickel ions and phosphate ions 16 ·The structural order of 4H2O has a great influence and directly affects HNaV6O 16 Performance of 4H2O as a cathode material for sodium-ion batteries;
[0036] (6) Effect of reaction time and temperature on the cobalt ion embedding in HNaV6O 16 The growth of 4H2O plays a key role. Too long or too short reaction time, too high or too low reaction temperature are not conducive to the assembly of a good micro-flower structure and directly affect the HNaV6O 16 Performance of 4H2O as a cathode material for sodium-ion batteries;
[0037] (7) Cobalt ions, nickel ions, and phosphate ions co-intercalate into HNaV6O 16 During the in-situ growth of 4H2O, the synergistic effect of the temperature field and pressure field generated by hydrothermal heat causes cobalt ions, nickel ions, and phosphate ions to form a 16 ·4H2O forms a strong chemical bond between the layers and always exists stably between the layers during the charge and discharge process;
[0038] (8) The atomic layer deposition technology used in the present invention can successfully deposit HNaV6O in which cobalt ions, nickel ions and phosphate ions are co-embedded by controlling the type of reaction source and the reaction temperature. 16·Al2O3, Fe2O3, ZnO, TiO2 and other metal oxides are successfully deposited on the surface of 4H2O powder. The deposited metal oxide coating effectively inhibits the volume expansion of the material during the charge and discharge process, and reduces the occurrence of side reactions between the electrolyte and the electrode material, thereby improving the charge and discharge efficiency and cycle stability of the positive electrode material;
[0039] (9) The product prepared by the present invention can show good performance when used as a positive electrode material for sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is the X-ray diffraction pattern of the product prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0041] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0042] The present invention provides a preparation method of atomic layer deposition synergistic doping modified sodium vanadate, using water as solvent, anhydrous sodium iodide and monohydrated vanadium oxyphosphate as sodium source, vanadium source and phosphorus source, and introducing cobalt acetate tetrahydrate and nickel acetate tetrahydrate, and realizing one-step hydrothermal synthesis of HNaV6O assembled by nanosheets and co-embedded with cobalt ions, nickel ions and phosphate ions by synergistic control of their concentration and ratio, reaction temperature, reaction time and other parameters. 16 ·4H2O nanoflower structure. This method has a simple reaction process, low temperature, easy control, and does not require large equipment and harsh reaction conditions. On this basis, the atomic layer deposition technology was used to successfully realize the cobalt ion, nickel ion and phosphate ion co-embedded HNaV6O with ultra-thin nanoscale metal oxides. 16 · Uniform coating of 4H2O cathode material, HNaV6O co-embedded with metal oxides, cobalt ions, nickel ions and phosphate ions 16 The bond between 4H2O is a chemical bond, not a physical bond;
[0043] The present invention also provides a method for applying the above product to a positive electrode material of a sodium ion battery, which can exhibit excellent electrochemical performance.
[0044] Example 1
[0045] Step 1, weigh 300 mg of vanadium oxyphosphate monohydrate, disperse it in 35 ml of deionized water, and ultrasonicate for 1 hour to obtain solution A;
[0046] Step 2, weighing 7.80 mg of cobalt acetate tetrahydrate and nickel acetate tetrahydrate and 92.80 mg of anhydrous sodium iodide and adding them to solution A to obtain solution B;
[0047] Step 3, sonicate solution B for 2 h, and the solution gradually changes from wine red to black;
[0048] Step 4, pour the ultrasonicated solution B into the 50 ml reactor liner, then fix the liner in the outer reactor, put it into a forced air drying oven, react at 150° C. for 12 h, and wash the product with water and alcohol alternately for 3 times;
[0049] Step 5: After vacuum drying, the product is collected and ground to obtain HNaV6O co-embedded with cobalt ions, nickel ions and phosphate ions. 16 4H2O powder sample;
[0050] Step 6: HNaV6O co-embedded with cobalt ions, nickel ions and phosphate ions 16 4H2O powder is placed in the ALD reaction chamber, evacuated and heated to 120°C;
[0051] Step 7: In a vacuum environment, inert gas carries TMA vapor and deposits it on HNaV6O co-embedded with cobalt ions, nickel ions and phosphate ions. 16 4H2O particle surface, duration 60s;
[0052] Step 8: The inert carrier gas at a specific flow rate transports the cobalt ions, nickel ions and phosphate ions into the HNaV6O 16 The physically adsorbed TMA on the surface of 4H2O particles was blown off, leaving a layer of chemically adsorbed TMA. The blowing time was 120s.
[0053] Step 9: Water uses its own vapor pressure to co-intercalate HNaV6O with cobalt ions, nickel ions and phosphate ions. 16 The TMA adsorbed on the surface of 4H2O particles undergoes redox reaction;
[0054] Step 10: The inert carrier gas at a specific flow rate transports the cobalt ions, nickel ions and phosphate ions into the HNaV6O 16 ·Blow away the byproducts and excess water molecules on the surface of 4H2O particles for 120s; after standing, purge the chamber with inert gas to complete an ALD cycle. Perform multiple cycles under the same deposition conditions to complete the deposition of Al2O3 of the specified thickness.
[0055] like Figure 1 As shown, all diffraction peaks can be well matched with HNaV6O 16 ·4H2O standard card PDF#49-0996. Due to the low content of introduced cobalt ions and nickel ions, HNaV6O 16 The crystal structure of 4H2O has not changed and the crystallinity is good. In addition, the deposited metal oxide is amorphous, so the diffraction peak corresponding to the oxide cannot be observed.
[0056] Example 2
[0057] Step 1, weigh 250 mg of vanadium oxyphosphate monohydrate, disperse it in 30 ml of deionized water, and ultrasonicate for 0.5 h to obtain solution A;
[0058] Step 2, weighing 7.50 mg of cobalt acetate tetrahydrate and nickel acetate tetrahydrate and 90 mg of anhydrous sodium iodide and adding them to solution A to obtain solution B;
[0059] Step 3, sonicate solution B for 1 h, and the solution gradually changes from wine red to black;
[0060] Step 4, pour the ultrasonicated solution B into the 50 ml reactor liner, then fix the liner in the outer reactor, put it into a forced air drying oven, react at 140° C. for 11 h, and wash the product alternately with 2 water and 2 alcohols;
[0061] Step 5: After vacuum drying, the product is collected and ground to obtain HNaV6O co-embedded with cobalt ions, nickel ions and phosphate ions. 16 4H2O powder sample;
[0062] Step 6: HNaV6O co-embedded with cobalt ions, nickel ions and phosphate ions 16 4H2O powder is placed in the ALD reaction chamber, evacuated and heated to 110°C;
[0063] Step 7: In a vacuum environment, inert gas carries TMA vapor and deposits it on HNaV6O co-embedded with cobalt ions, nickel ions and phosphate ions. 16 4H2O particle surface, duration 50s;
[0064] Step 8: The inert carrier gas at a specific flow rate transports the cobalt ions, nickel ions and phosphate ions into the HNaV6O 16 The physically adsorbed TMA on the surface of 4H2O particles was blown off, leaving a layer of chemically adsorbed TMA. The blowing time was 110s.
[0065] Step 9: Water uses its own vapor pressure to co-intercalate HNaV6O with cobalt ions, nickel ions and phosphate ions. 16 The TMA adsorbed on the surface of 4H2O particles undergoes redox reaction;
[0066] Step 10: The inert carrier gas at a specific flow rate transports the cobalt ions, nickel ions and phosphate ions into the HNaV6O 16 ·Blow away the byproducts and excess water molecules on the surface of 4H2O particles for 110 seconds; after standing, purge the chamber with inert gas to complete an ALD cycle. Perform multiple cycles under the same deposition conditions to complete the deposition of Al2O3 of the specified thickness.
[0067] Example 3
[0068] Step 1, weigh 350 mg of vanadium oxyphosphate monohydrate, disperse it in 40 ml of deionized water, and ultrasonicate for 1.5 hours to obtain solution A;
[0069] Step 2, weighing 8.0 mg of cobalt acetate tetrahydrate and nickel acetate tetrahydrate and 95 mg of anhydrous sodium iodide, and adding them to solution A to obtain solution B;
[0070] Step 3, sonicate solution B for 3 h, and the solution gradually changes from wine red to black;
[0071] Step 4, pour the ultrasonicated solution B into the 50 ml reactor liner, then fix the liner in the outer reactor, put it into a blast drying oven, react at 160° C. for 13 h, and wash the product with 4 water and 4 alcohols alternately;
[0072] Step 5: After vacuum drying, the product is collected and ground to obtain HNaV6O co-embedded with cobalt ions, nickel ions and phosphate ions. 16 4H2O powder sample;
[0073] Step 6: HNaV6O co-embedded with cobalt ions, nickel ions and phosphate ions 16 4H2O powder is placed in the ALD reaction chamber, evacuated and heated to 130°C;
[0074] Step 7: In a vacuum environment, inert gas carries TMA vapor and deposits it on HNaV6O co-embedded with cobalt ions, nickel ions and phosphate ions. 16 4H2O particle surface, duration 70s;
[0075] Step 8: The inert carrier gas at a specific flow rate transports the cobalt ions, nickel ions and phosphate ions into the HNaV6O 16 The physically adsorbed TMA on the surface of 4H2O particles was blown off, leaving a layer of chemically adsorbed TMA. The blowing time was 130s.
[0076] Step 9: Water uses its own vapor pressure to co-intercalate HNaV6O with cobalt ions, nickel ions and phosphate ions. 16 The TMA adsorbed on the surface of 4H2O particles undergoes redox reaction;
[0077] Step 10: The inert carrier gas at a specific flow rate transports the cobalt ions, nickel ions and phosphate ions into the HNaV6O 16 ·Blow away the byproducts and excess water molecules on the surface of 4H2O particles for 130 seconds; after standing, purge the chamber with inert gas to complete an ALD cycle. Perform multiple cycles under the same deposition conditions to complete the deposition of Al2O3 of the specified thickness.
Claims
1. A method for preparing modified sodium vanadate by atomic layer deposition and doping, characterized in that: Please follow the steps below to implement: Step 1, weighing vanadium oxyphosphate monohydrate, dispersing it in deionized water and ultrasonically treating it to obtain solution A; Step 2, weighing cobalt acetate tetrahydrate, nickel acetate tetrahydrate and anhydrous sodium iodide and adding them to solution A to obtain solution B; Step 3, subjecting solution B to ultrasonic treatment; Step 4, pour the ultrasonicated solution B into the inner lining of the reaction kettle, then fix the inner lining in the outer kettle, put it into a blast drying oven, dry it, and then wash it; Step 5: After vacuum drying, the product is collected and ground to obtain HNaV6O co-embedded with cobalt ions, nickel ions and phosphate ions. 16 4H2O powder sample; Step 6: HNaV6O co-embedded with cobalt ions, nickel ions and phosphate ions 16 4H2O powder is placed in the ALD reaction chamber, vacuumed and heated; Step 7: In a vacuum environment, inert gas carries TMA vapor and deposits it on HNaV6O co-embedded with cobalt ions, nickel ions and phosphate ions. 16 4H2O particle surface; Step 8: The inert carrier gas at a specific flow rate transports the cobalt ions, nickel ions and phosphate ions into the HNaV6O 16 ·4H2O The physically adsorbed TMA on the particle surface is blown off, leaving a layer of chemically adsorbed TMA; Step 9: Water uses its own vapor pressure to co-intercalate HNaV6O with cobalt ions, nickel ions and phosphate ions. 16 ·The TMA adsorbed on the surface of 4H2O particles undergoes redox reaction; Step 10: The inert carrier gas at a specific flow rate transports the cobalt ions, nickel ions and phosphate ions into the HNaV6O 16 ·Blow away the byproducts and excess water molecules on the surface of the 4H2O particles; after standing, purge the chamber with inert gas to complete an ALD cycle. Perform multiple cycles under the same deposition conditions to complete the deposition of Al2O3 of a specified thickness; In step 1, 250-350 mg of vanadium oxyphosphate monohydrate is weighed and dispersed in 30-40 mL of deionized water, and ultrasonicated for 0.5 h-1.5 h at a power of 80-120 W at room temperature; In step 2, 7.50-8.0 mg of cobalt acetate tetrahydrate and nickel acetate tetrahydrate and 90-95 mg of anhydrous sodium iodide are weighed and added to solution A to obtain solution B; Step 3 is as follows: subjecting solution B to ultrasonic treatment for 1 h to 3 h at a power of 80 to 120 W at room temperature until the solution gradually changes from wine red to black.
2. The method for preparing atomic layer deposition synergistically doped modified sodium vanadate according to claim 1, characterized in that: In step 4, the drying temperature is 140-160° C., the reaction time is 11-13 hours, and the washing process is specifically as follows: the product is washed alternately with water 2-4 times and alcohol 2-4 times.
3. The method for preparing atomic layer deposition synergistically doped modified sodium vanadate according to claim 1, characterized in that: The vacuum conditions in step 5 are: 50-70° C., drying for 11-13 hours, and before vacuum drying, sealing with plastic wrap, and piercing the plastic wrap.
4. The method for preparing atomic layer deposition synergistically doped modified sodium vanadate according to claim 1, characterized in that: In step 6, the powder sample is vibrated and dispersed before being added into the reaction chamber, and the temperature is raised to 110-130° C.; In step 7, the inert gas flow rate is 40 mL / min and the duration is 50 to 70 s.
5. The method for preparing atomic layer deposition synergistically doped modified sodium vanadate according to claim 1, characterized in that: In step 8, the inert gas flow rate is 80 mL / min, and the blow-off time is 110-130 s; In step 9, the water injection time is 60 seconds.
6. The method for preparing atomic layer deposition synergistically doped modified sodium vanadate according to claim 1, characterized in that: In step 10, the inert gas flow rate is 80 mL / min, and the inert gas introduction time is 110-130 s.
Citation Information
Patent Citations
Ultra-small nanosheet self-assembled flower-like VS2 powder and preparation method thereof
CN108585042A
Preparation method for sodium vanadium fluorophosphate positive electrode material
CN111086978A
Cited By
Graphene-sodium hydrogen vanadate hydrate heterostructure material rich in oxygen vacancies, preparation method and application of graphene-sodium hydrogen vanadate hydrate heterostructure material
CN121215718A